Islamic Populism in Rural Indonesia: An Agrarian Change Approach - Syaifullah, Khalid; Wahyuning Prasodjo, Nuraini; Sunito, Satyawan (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2022)
A massive demonstration in Jakarta called “Aksi Bela Islam” (Action to Defend Islam) marks a continuity of the Islamist currents in post-New Order Indonesia. Many observers called it “Islamic populism”, a populist, cross-class alliance on behalf of the Islamic masses or “ummah” against capitalist development that has marginalized Muslims in the struggle for access to economic and political resources. However, despite this refreshing approach, many studies on Islamic populism still concentrate on the state (instead of capital) and the urban areas in explaining the development of Islamic populism. This article, therefore, offers a different approach to analyzing Islamic populism through the understanding of capitalism as a social relation and shifts to the countryside as its empirical basis by focusing on the case study of Bulak village in West Java. By combining insights from the literature on agrarian change and populism as a political strategy and adopting qualitative methods namely in-depth interviews (including oral history) and field observation, this article found that contemporary Islamic populism in Indonesia is a result of the specific development of capitalist relations in the context of rural agrarian change. In addition, it also found that Islamic populism is not a phenomenon confined to the urban areas, since it also spreads to the countryside. Moreover, Islamic populism in the countryside has distinctiveness, related to context, social background, and the ways it is mobilized.